Study of Designing Electrical Energy Plants With Feedback Method From Generator Output - Samsurizal, Samsurizal; Makkulau, Andi; Fikri, Miftahul; Haidi, Junas; Hestiawan, Hendri (Politeknik Negeri Semarang, 2022)
The use of electricity has now become a primary need for people who are used for activities as an energy source such as: lights, air conditioners, water pumps, washing machines, TVs, etc. and the longer the need for electrical energy in Indonesia is increasing while power plants are constantly increasing, this forces the government to continue to build power plants to meet the needs of electrical energy in the community. Of course, the construction of this power plant uses very large costs and various obstacles, one of the obstacles is that fuel that used to be a power plant used a lot of oil, now switches to gas and coal to reduce high electricity production costs. The research method that will be carried out is by feeding the generator output back into a rotor drive energy source so that there is a continuous circulation of energy so that the generator output can be charged according to the remaining power capacity fed by the generator. Based on the test results, results were obtained using a 25 Watt DC motor when the input voltage was 12 Volts the power generated on the motor was 13.8 Watts with a motor speed of 768 rpm. Testing on an 800 Watt generator obtained a maximum rpm result of 764 and a vout of 13.8 volts. the highest input voltage (Vin) obtained was 10.06 volts, the output voltage (Vout) was 3.9 volts, and the power produced was 41.34 Watts. The prototype design that was tested produced energy even though the results were still not significant.